2022
DOI: 10.32604/cmc.2022.025202
|View full text |Cite
|
Sign up to set email alerts
|

Improved Archimedes Optimization Algorithm with Deep Learning Empowered Fall Detection System

Abstract: Human fall detection (FD) acts as an important part in creating sensor based alarm system, enabling physical therapists to minimize the effect of fall events and save human lives. Generally, elderly people suffer from several diseases, and fall action is a common situation which can occur at any time. In this view, this paper presents an Improved Archimedes Optimization Algorithm with Deep Learning Empowered Fall Detection (IAOA-DLFD) model to identify the fall/non-fall events. The proposed IAOA-DLFD technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The results showed that combining both models is efficient and practical to the developed system, with 92.5% accuracy. To identify fall/non-fall events, the research in [25] [26,27] has been used in this study. This dataset was acquired from 14 healthy individuals by using a wearable smartwatch.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that combining both models is efficient and practical to the developed system, with 92.5% accuracy. To identify fall/non-fall events, the research in [25] [26,27] has been used in this study. This dataset was acquired from 14 healthy individuals by using a wearable smartwatch.…”
Section: Related Workmentioning
confidence: 99%
“…The outcomes reveal that BiLSTM is a good model for handling missing values in wearable falling detection systems due to its ability to maintain long-term connectivity. The proposed study in [23] presented an improved Archimedes optimization method (IAOM) with DL augmented Fall detection model to distinguish between fall and non-fall events. The IAOM significantly enhances the detection of falls functionality by using a superior set of CapsNet hyperparameters.…”
Section: Related Workmentioning
confidence: 99%